2004
DOI: 10.1002/chem.200306048
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Transfer Agents as Catalysts for a Nucleophilic Substitution Reaction in Microemulsions

Abstract: The reaction between 4-tert-butylbenzyl bromide and potassium iodide was carried out in microemulsions based on different nonionic surfactants, and the reaction rates were compared with those obtained in two-phase systems with added phase-transfer agent, either a quaternary ammonium salt or a crown ether. The reactions were relatively fast in the microemulsions and extremely sluggish in the two-phase systems without additional phase-transfer agent. Addition of a phase-transfer agent did not accelerate the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Typical examples of their use include phase-transfer catalysts, [7] oxidant solubilizers, [8] membrane transport agents, [9] sequestering reagents, [10] ra-…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples of their use include phase-transfer catalysts, [7] oxidant solubilizers, [8] membrane transport agents, [9] sequestering reagents, [10] ra-…”
Section: Introductionmentioning
confidence: 99%
“…Considering the model S N 2 reaction between 4-tert-butylbenzyl bromide and potassium iodide the situation can be different. [27] They found that the conversion within a twophase system with addition of a PTA is just as fast as in a microemulsion system with PTA. In this case the total interfacial area does not determine the reaction rate and one may assume a fast and efficient extraction equilibrium, whereby the "chemical" reaction itself is the rate determining step.…”
Section: Discussion Epoxidation Of Trans-chalcone (I)mentioning
confidence: 99%
“…[41] The microemulsion was based on a chlorinated hydrocarbon and a sugar surfactant, octyl glucoside, which means that there were no counterions competing with the nucleophile at the oil-water interface. A quaternary ammonium salt, tetrabutylammonium hydrogen sulfate, was used as phase-transfer catalyst, both in an amount equimolar to the iodide and in a catalytic amount.…”
Section: Combining the Microemulsion Approach With Phase-transfer Catmentioning
confidence: 99%